INTERNATIONALLY LEGAL MEASURES TO COMBAT TERRORIST FINANCING - Yuniarti Yuniarti (Brawijaya Law Journal : Journal of Legal Studies, 2014)
Following the terrorist attacks in the USA on September 11th, 2001, it was discovered that money laundering was a significant source of finance for terrorists. Although, the amount of money that involve is not as involve as in drug and gun trafficking, terrorist financing had been the most important substance to be monitor. Further, various legal measures have been taken internationally in order to combat terrorist financing. This research analyses the legal measures that have been taken internationally and at EU level to combat terrorist financing.